Refractory hypercalcemia of malignancy: a problem with many potential roots - Farooki, Azeez (Frontiers in Endocrinology, 2023)
Hypercalcemia of malignancy (HCM) is a common clinical problem that is associated with considerable morbidity and negative effects on quality of life. Despite the availability of effective medical treatments for HCM, options are needed for cases that are refractory to conventional therapies. In this context, “refractory” refers to reasonable control of calcium in the setting of inpatient hospitalization (after receipt of standard of care therapies, such as continuous intravenous fluids, calcitonin, and intravenous bisphosphonates) with relapse into severe hypercalcemia within days or weeks of discharge from the hospital. Here we discuss drivers of hypercalcemia of malignancy and the physiologic mechanisms whereby they operate to increase serum calcium. Additionally, we discuss available, but sometimes overlooked treatments targeted to a given contributory mechanism and also briefly discuss potential future treatments in need of further study.